Evaluación de la contaminación sonora en los principales centros recreativos nocturnos de la ciudad de Morales - Vera Ledesma, Dhane (2015)
This research work called noise pollution evaluation in the main recreational nightlife centers of Morales City, San Martin province, San Martin Region, it was developed with the objective of evaluating the noise pollution in the main recreational nightlife centers of Morales city. The type of research is applied, given to the type of information that is presented in the report, will serve to get an idea of the current situation of Morales district in the sampling points (Recreational Centers at night), and to provide with knowledge of a systematic and methodical manner, for which have been developed tables and graphs. Found a total of five (05) sampling points of assessment in Morales city which were "Discotheque The Mega-Station", "the farm tourist recreation and Disco", "Disco Bunker Space", "Disco Anaconda" and "Video Corner Pub of the 80 'th", that have been evaluated with the sound level meter of property of the Consultancy Center for Research, Management and Environmental CEICA S.A. C. , on Friday, Saturday and Sunday in three shifts: the first round of 19:30 to 20:00 hours, the second shift of 22:30 to 23:00 hours, and the third shift of 02:30 to 03:00 p.m. the monitoring was carried out in days not holidays, to obtain results on an equal footing between sampling points. As a final conclusion it is noted that the noise pollution caused by the recreational nightlife centers that are found in the city of Morales, are surpassing the maximum permissible limits of 75 dba established in the Ordinance No. 004-MDM-2011 of Morales District Municipality, being the point 05 (Video Corner Pub of the 80 'th) the establishment with the highest pollution emissions and that is hurting the people that are in its range of emission, and in part of this pollution, are attributed as externa! agents to vehicles with their exhaust pipes open. Key words: noise pollution; recreational nightlife centers.